Retraction notice to “Machine learning based prediction and experimental validation of arsenite and arsenate sorption on biochars” [Sci. Total Environ. 904 (2023) 166678] - Wei Zhang; Waqar Muhammad Ashraf; Sachini Supunsala Senadheera; Daniel S. Alessi; Filip M.G. Tack; Yong Sik Ok (Science of The Total Environment, 2026)

DNA methylation as a biomarker of salinity and contaminant stress in mangrove crab Ucides occidentalis - Kim Pham; Andrée De Cock; Long Ho; Claudio Peter D'Incal; Wim Vanden Berghe; Dominguez Granda Luis; Filip M.G. Tack; Pieter Spanoghe; Peter L.M. Goethals (Marine Pollution Bulletin, 2026)

Valorization of reservoir bottom sediments as plant-growing media in agriculture and horticulture - Agnieszka Baran; Filip M. G. Tack; Antoine Delemazure; Jerzy Wieczorek; Katarzyna Szarłowicz (Journal of Soils and Sediments, 2026)

One-step carbonate-assisted in situ crosslinking of Fe(OH)3–Alginate for enhanced removal of Se and As from sulfate-rich wastewater - Jingya Ren; Dongqing Cai; Dongfang Wang; Xiaofei Wang; Filip M.G. Tack; Gijs Du Laing (Journal of Environmental Management, 2025)

Correction to: Harnessing green tide Ulva biomass for carbon dioxide sequestration - Jihae Park; Hojun Lee; De Saeger; Stephen Depuydt; Jana Asselman; Colin Janssen; Philippe M. Heynderickx; Di Wu; Frederik Ronsse; Filip M. G. Tack; Masanori Hiraoka; Lalit K. Pandey; et al. (Reviews in Environmental Science and Bio/Technology, 2024)

Harnessing green tide Ulva biomass for carbon dioxide sequestration - Jihae Park; Hojun Lee; Jonas De Saeger; Stephen Depuydt; Jana Asselman; Colin Janssen; Philippe M. Heynderickx; Di Wu; Frederik Ronsse; Filip M. G. Tack; Masanori Hiraoka; Lalit K. Pandey; et al. (Reviews in Environmental Science and Bio/Technology, 2024)

Impact of abiotic stressors on nutrient removal and rhizomicrobiome composition in floating treatment wetland with Equisetum hyemale - Nicole Nawrot; Przemysław Kowal; Ewa Wojciechowska; Ksenia Pazdro; Jolanta Walkusz-Miotk; Sławomir Ciesielski; Filip M.G. Tack (Science of The Total Environment, 2024)

RETRACTED: Machine learning based prediction and experimental validation of arsenite and arsenate sorption on biochars - Wei Zhang; Waqar Muhammad Ashraf; Sachini Supunsala Senadheera; Daniel S. Alessi; Filip M.G. Tack; Yong Sik Ok (Science of The Total Environment, 2023)

Thermochemical upcycling of food waste into engineered biochar for energy and environmental applications: A critical review - Xiangzhou Yuan; Yafei Shen; Piumi Amasha Withana; Ondřej Mašek; Carol Sze Ki Lin; Siming You; Filip M.G. Tack; Yong Sik Ok (Chemical Engineering Journal, 2023)

Sedimentation of metals in Sundarban mangrove ecosystem: Dominant drivers and environmental risks - Jayjit Majumdar; Jayanta Kumar Biswas; Subhas Chandra Santra; A. L. Ramanathan; Filip M. G. Tack (Environmental Geochemistry and Health, 2023)

Health risk-benefit assessment of the commercial red mangrove crab: Implications for a cultural delicacy - Andrée De Cock; Marie Anne Eurie Forio; Siska Croubels; Luis Dominguez-Granda; Liesbeth Jacxsens; Carl Lachat; Heydi Roa-López; Jenny Ruales; Victoria Scheyvaerts; Michelle Carolina Solis Hidalgo; Pieter Spanoghe; Filip M.G. Tack; et al. (Science of The Total Environment, 2023)

A state-of-the-art review on cadmium uptake, toxicity, and tolerance in rice: From physiological response to remediation process - Pedda Ghouse Peera Sheikh Kulsum; Rubina Khanam; Shreya Das; Amaresh Kumar Nayak; Filip M.G. Tack; Erik Meers; Meththika Vithanage; Mohammad Shahid; Anjani Kumar; Sukalyan Chakraborty; Tanushree Bhattacharya; Jayanta Kumar Biswas (Environmental Research, 2023)

The nutritional quality of the red mangrove crab (Ucides occidentalis), harvested at two reserves in the Guayas estuary - Andrée De Cock; Marie Anne Eurie Forio; Bruno De Meulenaer; Filip Tack; Luis Dominguez-Granda; Peter L.M. Goethals (Food Chemistry, 2023)

Metal contamination in sediments of dam reservoirs: A multi-facetted generic risk assessment - Agnieszka Baran; Filip M.G. Tack; Antoine Delemazure; Jerzy Wieczorek; Marek Tarnawski; Gavin Birch (Chemosphere, 2023)

Influence of biochar on trace element uptake, toxicity and detoxification in plants and associated health risks: A critical review - Natasha Natasha; Muhammad Shahid; Sana Khalid; Irshad Bibi; Muhammad Asif Naeem; Nabeel Khan Niazi; Filip M. G. Tack; James Anthony Ippolito; Jörg Rinklebe (Critical Reviews in Environmental Science and Technology, 2022)

Evaluating the adsorptive capacity of three Tunisian clays deposits for several potentially toxic metals in phosphogypsum waste - Kawther Ben Moussa; Saifeddine Eturki; Reinhart Van Poucke; Samuel Bodé; Johan De Grave; Eric Van Ranst; Filip M. G. Tack; Mohamed Moussa (Arabian Journal of Geosciences, 2022)

Cadmium stress in plants: A critical review of the effects, mechanisms, and tolerance strategies - Taoufik El Rasafi; Abdallah Oukarroum; Abdelmajid Haddioui; Hocheol Song; Eilhann E. Kwon; Nanthi Bolan; Filip M. G. Tack; Abin Sebastian; M. N. V. Prasad; Jörg Rinklebe (Critical Reviews in Environmental Science and Technology, 2022)

Effects of selenium on the uptake of toxic trace elements by crop plants: A review - Muhammad Rizwan; Shafaqat Ali; Muhammad Zia ur Rehman; Jörg Rinklebe; Daniel C. W. Tsang; Filip M. G. Tack; Ghulam Hasan Abbasi; Afzal Hussain; Avanthi Deshani Igalavithana; Byung Cheon Lee; Yong Sik Ok (Critical Reviews in Environmental Science and Technology, 2021)

Solid fraction of separated digestate as soil improver: implications for soil fertility and carbon sequestration - Caleb Elijah Egene; Ivona Sigurnjak; Inge C. Regelink; Oscar F. Schoumans; Fabrizio Adani; Evi Michels; Steven Sleutel; Filip M. G. Tack; Erik Meers (Journal of Soils and Sediments, 2021)
Purpose This study investigated the C and N mineralisation potential of solid fractions (SFs) from co-digestated pig manure after P-stripping (P-POOR SF) in comparison with P-rich SFs, as a means to estimate their organic matter stability in soil. Compost (COMP) and biochar (BCHR) (made from P-POOR SF) were also included in the study as reference biosolids. Methods The SFs were incubated in a sandy-loam soil under moist conditions to determine production of CO 2 and mineral N. At specified intervals, CO 2 evolution in the mixtures was measured via the alkali trap method and titration over a period of 81 days, while mineral N was measured using a flow analyser after KCl extraction over a period of 112 days. Results The various SFs showed similar patterns of C mineralisation (15–26% of added total C in 81 days) that were clearly higher than for COMP and BCHR (6% and 7%, respectively). Temporary N immobilisation was observed in biosolids with a high C/N ratio. The effective organic matter (EOM) of the SFs was calculated based on the C mineralisation data and varied between 130 and 369 kg Mg −1 . Conclusions The SF with a reduced P content had a high EOM/P ratio which is beneficial in areas where P status of the soil is already high. Moreover, the N mineralisation patterns confirm that a high C/N ratio may also reduce risks for N leaching due to temporary N immobilisation.

Field trials of phytomining and phytoremediation: A critical review of influencing factors and effects of additives - Liuwei Wang; Deyi Hou; Zhengtao Shen; Jin Zhu; Xiyue Jia; Yong Sik Ok; Filip M. G. Tack; Jörg Rinklebe (Critical Reviews in Environmental Science and Technology, 2020)

Application of biochars and solid fraction of digestate to decrease soil solution Cd, Pb and Zn concentrations in contaminated sandy soils - Reinhart Van Poucke; Caleb E. Egene; Simon Allaert; Manhattan Lebrun; Sylvain Bourgerie; Domenico Morabito; Yong Sik Ok; Frederik Ronsse; Erik Meers; Filip M.G. Tack (Environmental Geochemistry and Health, 2020)

Trace Elements in Potato - Filip M. G. Tack (Potato Research, 2014)

Opportunities for domesticating the African baobab (Adansonia digitata L.): multi-trait fruit selection - David J. Simbo; Sebastiaan De Smedt; Nina Van den Bilcke; Bruno De Meulenaer; John Van Camp; Veronique Uytterhoeven; Filip Tack; Roeland Samson (Agroforestry Systems, 2013)

Integrated Constructed Wetlands (ICW): Ecological Development in Constructed Wetlands for Manure Treatment - Pieter Boets; Evi Michels; Erik Meers; Koen Lock; Filip M. G. Tack; Peter L. M. Goethals (Wetlands, 2011)

Effects of Vegetation, Season and Temperature on the Removal of Pollutants in Experimental Floating Treatment Wetlands - Annelies M. K. Van de Moortel; Erik Meers; Niels De Pauw; Filip M. G. Tack (Water, Air, & Soil Pollution, 2010)

Effect of Water Table Level on Metal Mobility at Different Depths in Wetland Soils of the Scheldt Estuary (Belgium) - Gijs Du Laing; Erik Meers; Marjan Dewispelaere; Jörg Rinklebe; Bart Vandecasteele; Marc G. Verloo; Filip M. G. Tack (Water, Air, & Soil Pollution, 2009)

Short-Rotation Coppice of Willow for Phytoremediation of a Metal-Contaminated Agricultural Area: A Sustainability Assessment - Nele Witters; Stijn Van Slycken; Ann Ruttens; Kristin Adriaensen; Erik Meers; Linda Meiresonne; Filip M. G. Tack; Theo Thewys; Erik Laes; Jaco Vangronsveld (BioEnergy Research, 2009)

Metal accumulation in intertidal marshes: Role of sulphide precipitation - Gijs Laing; Benjamin Meyer; Erik Meers; Els Lesage; Annelies Moortel; Filip M. G. Tack; Marc G. Verloo (Wetlands, 2008)

Extraction of labile metals from solid media by dilute hydrochloric acid - Ross A. Sutherland; Filip M. G. Tack (Environmental Monitoring and Assessment, 2008)

Sequential Extraction of Lead from Grain Size Fractionated River Sediments Using the Optimized BCR Procedure - Ross A. Sutherland; Filip M. G. Tack (Water, Air, & Soil Pollution, 2007)

Tertiary treatment of the liquid fraction of pig manure with Phragmites australis - Erik Meers; Diederik P. L. Rousseau; Nathalie Blomme; Els Lesage; Gijs Du Laing; Filip M. G. Tack; Marc G. Verloo (Water, Air, & Soil Pollution, 2005)

Assessment of the Pollution Status of Alluvial Plains: A Case Study for the Dredged Sediment-Derived Soils Along the Leie River - Bart Vandecasteele; Paul Quataert; Bruno De Vos; Filip M. G. Tack (Archives of Environmental Contamination and Toxicology, 2004)

Cd and Zn Concentration in Hybrid Poplar Foliage and Leaf Beetles Grown on Polluted Sediment-Derived Soils - Bart Vandecasteele; Raf Lauriks; Bruno De Vos; Filip M. G. Tack (Environmental Monitoring and Assessment, 2003)

Metal Extraction from Road Sediment using Different Strength Reagents: Impact on Anthropogenic Contaminant Signals - Ross A. Sutherland; Filip M. G. Tack; Christina A. Tolosa; Marc G. Verloo (Environmental Monitoring and Assessment, 2001)